The explanatory power of social capital in determining knowledge sharing in higher education: A case from Saudi Arabia - Almuqrin, Abdullah; (Justin) Zhang, Zuopeng; Alzamil, Aljawharah; Mutambik, Ibrahim; Alhabeeb, Abdullah (Malaysian Journal of Library and Information Science, 2020)
Knowledge sharing strengthens individual creativity, critical thinking and innovation. It also improves research and development endeavors, performance and productivity at the organizational level. Knowledge sharing decreases the amount of red-tape faced by organizations, firms and individuals in achieving economic, as well as social improvements. Notwithstanding the plethora of empirical studies on knowledge sharing determinants, much confusion has been produced by differing conclusions. Using original data collected via questionnaires from a sample of 404 participants at a Saudi public university, this analysis tested the effect of social capital on knowledge sharing intentions and behaviors. Findings from the Structural Equation Model found support to the hypotheses claiming positive associations between social ties, trust, identification, reciprocity, shared language, and shared vision and knowledge sharing. This study proposes a practice-based strategy for higher learning institutions to improve knowledge sharing behaviors built on the two components of enhancing enabling environments and technical skills. On the theoretical level, this study argues that the effects of social capital constructs differ with respect to the context considered. In higher education, social capital is thought to have a weak significant positive explanatory power on knowledge sharing behaviors.